PENYULUHAN GIZI MENGGUNAKAN MEDIA E- BOOKLET DENGAN METODE PENDAMPINGAN TERHADAP ASUPAN ENERGI DAN PROTEIN PADA REMAJA PUTRI KURANG ENERGI KRONIS (KEK) - Azarine Aqilah Haya; Nitta Isdiany; Yohannes Willihelm Saleky; Suparman Suparman (Jurnal Gizi dan Dietetik, 2022)
Inadequate intake of nutrients obtained during adolescent girls will have an impact on health in the next phase of life, namely adults (pregnant women) and the elderly. Lack of nutrient intake will cause various kinds of nutritional problems, one of which is chronic energy deficiency (CED). The purpose of this study was to determine the effect of nutritional counseling using e-booklet media with mentoring methods on energy and protein intake in adolescent girls with chronic energy deficiency (CED) in Indonesia. SMAN 2 Cimahi which will be held in September – October 2021. The design of this research is a pre-experimental one group pre-post test design. The number of research samples is 25 people. Energy and protein intake data were taken by interview using a 24-hour recall form. The results showed that the average energy intake of the sample before the intervention was 1167.32 Kcal and after the intervention was 1745.76 Kcal. The average protein intake of the sample before the intervention was 39.76 grams and after the intervention was 58.76 grams. The results of the t-dependent test showed that there was an effect of nutritional counseling using e-booklet media with mentoring methods on energy intake (p = 0.000) and protein (p = 0.000) in the sample. It can be concluded that there is an effect of nutrition counseling using e-booklet media with mentoring methods on energy and protein intake of adolescent girls with chronic energy deficiency (CED). Further research can be compared using the control group.